Modified CMC for silicon-doped negative electrode aqueous slurry of lithium battery and preparation method thereof

CN122897945APending Publication Date: 2026-10-13CHANGSHU WEIYI TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611237688.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]针对现有技术中锂电池负极水性粘结体系存在的CMC功能单一、接枝改性CMC多为钠盐型且不具备锂离子传输功能、粘结剂分子链缺乏适应硅体积膨胀的动态可逆交联结构、高取代度CMC接枝位点密度低且吸水性强等问题,本发明的目的在于提供一种锂电池掺硅负极水性浆料用改性CMC及其制备方法

Benefits of technology

本发明选用取代度0.6~0.8的中低取代度羧甲基纤维素作为接枝主链,从主链层面同时解决了接枝位点不足与吸水性强两个相互关联的问题。由于每个脱水葡萄糖单元上平均仅取代0.6~0.8个羧甲基,主链上保留了大量游离羟基,为接枝共聚反应提供了密集的接枝位点,使功能侧链能够以较高接枝率均匀引入;同时,较低的羧甲基密度意味着主链亲水性显著弱于常规高取代度CMC,所得粘结剂吸水率低、对浆料水分及环境湿度的敏感性小,且增稠能力更强、达到同等浆料粘度所需的添加量更少,有利于提高电极中活性物质的占比。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897945A_ABST
    Figure CN122897945A_ABST
Patent Text Reader

Abstract

The application discloses a modified CMC for a silicon-doped negative electrode water-based slurry of a lithium battery and a preparation method thereof, and belongs to the technical field of modified carboxymethyl cellulose. The modified CMC takes a medium-low degree of substitution CMC as a main chain, and copolymer side chains are grafted on the main chain; the copolymer side chains comprise N-vinyl pyrrolidone, lithium acrylate, 3-acrylamido phenyl boronic acid and glycerol monomethyl methacrylate structural units. The modified CMC integrates thickening rheology, conductive agent dispersion, lithium ion transmission and dynamic crosslinking functions in the same molecule, can simplify a slurry formula, avoid multi-component migration and phase separation, and effectively buffer volume expansion of silicon particles in the silicon-doped negative electrode, so that the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of modified carboxymethyl cellulose technology, specifically relating to a modified CMC for silicon-doped anode aqueous slurry of lithium batteries and its preparation method. Background Technology

[0002] Lithium-ion batteries, due to their high energy density, long cycle life, and lack of memory effect, have become the mainstream energy storage devices in consumer electronics, electric transportation, and energy storage. The anode material is one of the key materials affecting battery energy density. Currently, commercially available anode materials are mainly graphite, but its actual specific capacity is approaching its theoretical limit of 372 mAh / g, making it difficult to meet the development needs of high-energy-density batteries. Silicon, with a theoretical specific capacity as high as 4200 mAh / g, is considered the most promising anode material for next-generation high-energy-density lithium-ion batteries. However, silicon undergoes volume expansion and contraction of up to approximately 300% during lithium insertion / extraction, leading to silicon particle pulverization, conductive network damage, and repeated rupture and regeneration of the solid electrolyte interface film, resulting in rapid capacity decay and severely restricting the large-scale application of silicon-based anodes. At present, incorporating silicon suboxide or silicon-carbon materials into graphite at a ratio of 3% to 15% to form silicon-doped anodes is the mainstream transitional solution that balances energy density and cycle performance. However, as the silicon doping ratio increases, the structural damage caused by silicon volume expansion remains a prominent issue.

[0003] Although the binder accounts for only 2% to 5% of the electrode's mass, it plays a crucial role in maintaining the integrity of the electrode structure, ensuring conductive contact between the active material and the conductive agent, and stabilizing the electrode / electrolyte interface. For silicon-doped anodes, the binder also needs to maintain the stability of the electrode structure under repeated and drastic volume changes of silicon particles, and its performance directly affects the cycle life of the battery. Currently, graphite anodes generally use an aqueous binder system composed of carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) emulsions, in which CMC mainly plays a role in thickening, dispersing, and assisting in bonding. Furthermore, the degree of substitution of conventional commercial CMC is usually 0.7 to 1.2, with most of the hydroxyl groups on the molecular chain occupied by carboxymethyl groups, resulting in a small number of free hydroxyl groups. Its function is singular, providing only rheological regulation and limited binding force, which is insufficient to meet the requirements of silicon-doped anodes.

[0004] To improve adhesive performance, various attempts have been made in the prior art. For example, Chinese patent CN105504169A discloses an adhesive that covalently grafts sodium carboxymethyl cellulose (CMC) onto sodium polyacrylate, thereby improving adhesive strength by grafting sodium polyacrylate side chains onto the CMC backbone; however, the side chains of this type of adhesive are sodium salt polymers, which will cause Na... +Impurities are introduced into the battery system, and their side chains lack the function of dispersing conductive agents and transporting lithium ions. For example, existing research reports on maleic anhydride copolymer binders such as poly(isobutylene-alt-maleic anhydride) and poly(ethylene-alt-maleic anhydride), as well as aqueous copolymer binders containing sulfonic acid groups, utilizing carboxyl or sulfonic acid groups to improve adhesion and lithium-ion transport performance; however, these binders are fully synthetic main-chain polymers and do not possess thickening rheological functions themselves, still requiring compounding with CMC. Furthermore, their molecular chains have a linear permanent structure and lack reversible crosslinking units capable of dynamically responding to silicon volume expansion. In addition, existing technologies also involve simple physical blending of carboxymethyl cellulose with polymers such as povidone and polyacrylic acid to improve dispersion or adhesion performance; however, in physically blended systems, the polymer components are prone to migration and phase separation, resulting in poor slurry stability and batch-to-batch consistency, and limited improvement in electrochemical performance.

[0005] In summary, the existing aqueous binder system for lithium battery anodes still has the following shortcomings: (1) The CMC has a single function, and the dispersion of conductive carbon materials requires the addition of dispersants, resulting in complex slurry formulations; (2) Grafted modified CMCs are mostly sodium salts, which easily introduce Na into the battery system. + Impurities, and the side chains do not have lithium-ion transport function; (3) Existing binder molecular chains are all linear permanent structures, lacking the ability to adapt to the volume expansion of silicon particles; (4) Conventional high-substitution degree CMC has few free hydroxyl groups and low grafting site density, which is not conducive to achieving high-density functionalization through grafting modification, and has strong water absorption, which is not conducive to the control of electrode moisture. Therefore, developing a multifunctional waterborne binder that integrates thickening rheology, conductive agent dispersion, lithium-ion transport and dynamic crosslinking functions is of great significance for improving the electrochemical performance of silicon-doped anodes. Summary of the Invention

[0006] To address the problems of existing aqueous binder systems for lithium-ion battery anodes, such as the single function of the CMC (conductor modifier), the fact that most grafted modified CMCs are sodium salts lacking lithium-ion transport capabilities, the lack of dynamically reversible cross-linking structures in the binder molecular chains to adapt to silicon volume expansion, and the low density and high water absorption of grafting sites in high-substitution CMCs, this invention aims to provide a modified CMC for aqueous slurry of silicon-doped anodes in lithium-ion batteries and its preparation method. This modified CMC integrates thickening rheology, conductive agent dispersion, lithium-ion transport, and dynamic cross-linking functions into a single molecule, simplifying slurry formulation, avoiding multi-component migration and phase separation, and effectively buffering the volume expansion of silicon particles in the silicon-doped anode, thereby improving the cycle performance of the battery.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a modified CMC for use in aqueous slurry of silicon-doped negative electrode for lithium batteries. The modified CMC has a medium-low degree of substitution CMC as the main chain, and copolymer side chains are grafted onto the main chain. The copolymer side chains contain N-vinylpyrrolidone, lithium acrylate, 3-acrylamidophenylboronic acid and glycerol monomethacrylate structural units.

[0008] Preferably, the degree of substitution of the medium-low degree CMC is 0.6 to 0.8, and the grafting rate of the modified CMC is 50% to 250%.

[0009] Preferably, the molar ratio of N-vinylpyrrolidone, lithium acrylate, 3-acrylamidophenylboronic acid and glycerol monomethacrylate is (60~80):(15~30):(2~5):(2.4~7.5).

[0010] Secondly, the present invention provides a method for preparing modified CMC for the aqueous slurry of silicon-doped anode in lithium batteries, comprising the following steps: (1) Dissolve carboxymethyl cellulose in deionized water to prepare a solution with a concentration of 0.5~2.0wt%, and heat it to 40~50℃ under nitrogen protection; (2) Add the total amount of N-vinylpyrrolidone monomer and glycerol monomethacrylate accounting for 1 / 3 to 2 / 3 of the total amount of feed; (3) Add some initiator and add lithium acrylate aqueous solution in batches or slowly and continuously to the reaction system within 0~90 min; add initiator and the full amount of 3-acrylamidophenylboronic acid solution and the remaining glycerol monomethacrylate within 60~90 min of reaction; (4) The reaction is carried out at 40~50℃ under nitrogen protection. The total reaction time from the addition of the initiator is 2~5h. (5) The reaction was terminated, and the modified CMC was obtained by precipitation, washing, purification and drying.

[0011] Preferably, the lithium acrylate aqueous solution is prepared by neutralizing acrylic acid with LiOH to a pH of 7.0-8.0, and is prepared before use; the 3-acrylamidophenylboronic acid solution is prepared by adding 3-acrylamidophenylboronic acid to deionized water, adjusting the pH to 8-8.5 with dilute LiOH solution to dissolve it, and is prepared before use; the initiator is ammonium persulfate or an ammonium persulfate / ascorbic acid redox system, with a total amount of 0.5%-3% of the total monomer mass, added in two parts, the first at the beginning of the reaction and the second at 60 min of the reaction.

[0012] Preferably, the purification includes methanol Soxhlet extraction and dialysis, wherein the dialysis is performed under pH ≤ 7 conditions, and the dialysis uses a dialysis bag with a molecular weight cutoff of 8000~14000 Da; the drying is freeze drying or vacuum drying at ≤ 40°C.

[0013] Thirdly, this invention protects the application of the modified CMC or the modified CMC prepared by the above preparation method in the preparation of aqueous slurry for silicon-doped anodes of lithium batteries. Specifically, the modified CMC is used in combination with styrene-butadiene rubber emulsion, and the active material of the silicon-doped anode includes graphite and silicon-oxygen materials, wherein the silicon-oxygen materials account for 3% to 15% of the total mass of the active materials.

[0014] Preferably, the slurry also contains hydrolyzed styrene-maleic anhydride copolymer, which is then cured at 100-120°C after coating, so that the hydrolyzed styrene-maleic anhydride copolymer undergoes in-situ esterification crosslinking with the modified CMC.

[0015] Fourthly, the present invention also protects a lithium battery negative electrode sheet, comprising the modified CMC described above or the modified CMC prepared by the preparation method described above, and a lithium-ion battery comprising the lithium battery negative electrode sheet described above.

[0016] Beneficial effects

[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention selects carboxymethyl cellulose (CMC) with a substitution degree of 0.6-0.8 as the grafting backbone, simultaneously addressing the two interrelated problems of insufficient grafting sites and high water absorption at the backbone level. Since each dehydrated glucose unit has an average substitution of only 0.6-0.8 carboxymethyl groups, the backbone retains a large number of free hydroxyl groups, providing dense grafting sites for the graft copolymerization reaction, allowing functional side chains to be uniformly introduced with a high grafting rate. Simultaneously, the lower carboxymethyl density means that the backbone's hydrophilicity is significantly weaker than that of conventional high-substitution CMC, resulting in a binder with low water absorption, less sensitivity to slurry moisture and environmental humidity, stronger thickening ability, and requiring less addition to achieve the same slurry viscosity, which is beneficial for increasing the proportion of active materials in the electrode.

[0018] In terms of side-chain functional design, this invention covalently integrates dispersion, interface anchoring, and ion transport functions into the same grafted side chain. The structural unit derived from N-vinylpyrrolidone contains a pyrrolidone ring, exhibiting good affinity for carbonaceous materials such as graphite and conductive carbon black, and can play a dispersing and stabilizing role within the molecule without the need for external dispersants. The structural unit derived from lithium acrylate contains lithium carboxylic acid groups, which can form hydrogen bonds and ion-dipole interactions with the abundant silanol groups on the SiOx surface, achieving strong anchoring of silicon-based active particles and simultaneously constructing Li within the electrode. +The presence of conductive sites is beneficial for improving interfacial ion transport kinetics; the use of lithium salt form also avoids the introduction of sodium ions, eliminating the need for Na+. + The risk of preferential reduction and deterioration of SEI film stability at low negative electrode potentials. The aforementioned functional units are all covalently connected to the main chain, overcoming the inherent defects of uneven distribution of functional components, easy phase separation, and difficulty in synergistic effect in existing physical blend systems.

[0019] To address the significant volume changes of silicon-based anodes during charge and discharge, this invention constructs a dynamic, reversible crosslinked network based on borate ester bonds within the binder molecule by combining 3-acrylamidophenylboronic acid and glycerol monomethacrylate as structural units. The phenylboronic acid groups and the cis-1,2-diol provided by glycerol monomethacrylate form borate ester covalent bonds in the electrode environment. These bonds are reversible: when the silicon-based active particles expand and the binder network is subjected to stress, the borate ester bonds preferentially break as sacrificial bonds to dissipate energy; when the silicon-based active particles shrink, the borate acid reforms through intramolecular / intermolecular transesterification mechanisms, forming new borate ester crosslinking points and restoring the network topology. This process requires no water, and the low water activity environment helps suppress the hydrolysis side reactions of the borate ester, ensuring the dynamic stability of the crosslinked network. This dynamic crosslinking mechanism enables the bonding network to maintain structural integrity under repeated volume changes of silicon particles, achieving self-healing and thus continuously constraining silicon particles and maintaining electrode structural integrity during long-term cycling. Simultaneously, the BO-Si bonds formed between borate groups and hydroxyl groups on the silicon surface provide additional anchoring sites for the binder to the silicon phase. This mechanism overcomes the shortcomings of existing CMC-based binders, which can only perform static bonding and cannot adapt to the volume changes of silicon-based negative poles.

[0020] At the preparation method level, this invention addresses the significant difference in polymerization reactivity between N-vinylpyrrolidone and acrylic monomers by employing a combination of time-sharing and starvation feeding methods. This ensures that the fast monomer remains at a low concentration throughout the reaction, while the slow monomer is preferentially grafted, guaranteeing the controllable composition and uniform distribution of the four structural units in the side chain. The preparation process uses an initiation system free of metal ions, supplemented by a deep purification step combining solvent precipitation, Soxhlet extraction, and dialysis, reducing the residual monomer and metal impurity content of the product to battery-grade levels. All reactions are carried out in an aqueous phase at a mild temperature, making the process simple and suitable for industrial scale-up.

[0021] At the application level, the modified CMC of this invention can be used in combination with flexible binders such as styrene-butadiene latex: the modified CMC molecular chain is responsible for anchoring, dispersing, and dynamically crosslinking the silicon and carbon phases, while the styrene-butadiene latex provides adhesion to the current collector and electrode flexibility. Together, they ensure both peel strength and cycle stability of the electrode. Furthermore, hydrolyzed styrene-maleic anhydride copolymer can be introduced during the slurry preparation stage. This copolymer exists in the slurry as a water-soluble salt and does not affect the rheological processing properties of the slurry. During the electrode drying and curing stage (100~120℃), the maleic acid ring-closed regenerated anhydride groups undergo in-situ esterification crosslinking with the free hydroxyl groups retained on the modified CMC main chain and the diols in the glycerol monomethacrylate structural units, forming an irreversible covalently reinforced network. This further improves the cohesive strength of the electrode and the electrolyte swelling resistance of the binder network. The resulting negative electrode and the lithium-ion battery containing this electrode exhibit improved cycle life and structural stability in a silicon-doped system. Attached Figure Description

[0022] Figure 1 The Fourier transform infrared (FTIR) spectrum of the modified CMC is shown. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0024] Unless otherwise specified, the experimental methods used in the embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0025] The raw materials and equipment used in the embodiments and comparative examples are described below: Medium to low degree of substitution CMC: substitution degree 0.6~0.8, 1% aqueous solution viscosity (25℃) 1000~1300mPa·s, battery grade (Fe≤10 ppm, magnetic foreign matter controlled), Changshu Weiyi Technology Co., Ltd.

[0026] High-substitution CMC: Substitution degree 0.9~1.2, 1% aqueous solution viscosity (25℃) 1500~2500mPa·s, battery grade (Fe≤ 10 ppm, magnetic foreign matter controlled), Changshu Weiyi Technology Co., Ltd.

[0027] N-Vinylpyrrolidone (NVP): The middle fraction was obtained by vacuum distillation at 14 mmHg and 55 °C to remove polymerization inhibitors and impurities.

[0028] Lithium acrylate solution: Dissolve 5.8g of acrylic acid (AA) in 15mL of deionized water, and dissolve 3.4g of LiOH·H2O in 15mL of deionized water. Control the temperature in an ice bath at <20℃. Slowly add LiOH·H2O solution to the acrylic acid solution, stirring continuously and monitoring the pH during the addition process. The lithium acrylate solution is obtained when the final pH is 7.0~8.0. Prepare and use immediately.

[0029] Glyceryl monomethacrylate: Commercially available. Before use, the polymerization inhibitor should be removed by an alkaline alumina column.

[0030] 3-Acrylamidophenylboronic acid: CAS: 99349-68-5, commercially available.

[0031] Deionized water: conductivity ≤1μS / cm.

[0032] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.

[0033] Example 1

[0034] A modified CMC for use in an aqueous slurry of silicon-doped anode for lithium batteries is prepared as follows: Add 10 parts by mass of low-substituted CMC to deionized water to prepare a 1 wt% solution. Stir and dissolve at 45°C, and purge with nitrogen for 30 min. Add the full amount of N-vinylpyrrolidone monomer and half the amount of glycerol monomethacrylate monomer to the CMC solution, where the total monomer to CMC mass ratio is 4:1; the molar ratio of N-vinylpyrrolidone, lithium acrylate, 3-acrylamidophenylboronic acid, and glycerol monomethacrylate is 70:22:3.5:4.5; add ammonium persulfate as an initiator at 1% of the total monomer mass. Stir under nitrogen protection at 45°C, and add lithium acrylate solution dropwise to the reaction system at a uniform rate over 0-90 min. After 60 min of reaction, add 0.5% of the initiator as an initiator. Dissolve 3-acrylamidophenylboronic acid in deionized water and adjust the pH to 8-8.5 with dilute LiOH solution to dissolve it. Simultaneously add the entire 3-acrylamidophenylboronic acid monomer solution and the remaining half of the glycerol monomethacrylate monomer over 60-90 min. The total reaction time is controlled at 4 hours. After the reaction was completed, hydroquinone (0.08% of the total monomer mass) was added to terminate the reaction. The reaction solution was slowly poured into 4 times its volume of ethanol under stirring to precipitate the product, which was then collected by filtration. The precipitate was washed four times with 75% ethanol aqueous solution to remove residual monomers. PVP homopolymer was removed by Soxhlet extraction with methanol for 24 hours. Dialysis was performed for 60 hours using a dialysis bag with a molecular weight cutoff of 10000 Da. During dialysis, the pH of the dialysis water was adjusted to 6-7 with dilute acid or dilute LiOH solution to remove lithium acrylate homopolymers and other water-soluble homopolymers, residual monomers, and inorganic salts. The residual NVP was controlled to be ≤0.1%, residual lithium acrylate ≤0.1%, and Na... + K + Total content ≤500ppm, Fe ≤10ppm. The dialysate is concentrated, freeze-dried to moisture content ≤8%, and then pulverized through a 100-mesh sieve.

[0035] Example 2

[0036] Compared with Example 1, the difference is that the mass ratio of total monomer to CMC is modified to 3:1.

[0037] Example 3

[0038] Compared with Example 1, the difference is that the mass ratio of total monomers to CMC is modified to 6:1.

[0039] Example 4

[0040] Compared with Example 1, the difference is that the molar ratio of N-vinylpyrrolidone, lithium acrylate, 3-acrylamidophenylboronic acid and glycerol monomethacrylate is modified to 80:15.6:2:2.4.

[0041] Example 5

[0042] Compared with Example 1, the difference is that the molar ratio of N-vinylpyrrolidone, lithium acrylate, 3-acrylamidophenylboronic acid and glycerol monomethacrylate is modified to 60:27.5:5:7.5.

[0043] Comparative Example 1 Compared with Example 1, the difference is that the CMC with low to medium substitution degree is replaced with the CMC with high substitution degree.

[0044] Comparative Example 2 Compared with Example 1, the difference is that 3-acrylamidophenylboronic acid and glycerol monomethacrylate are not added, and the molar ratio of N-vinylpyrrolidone to lithium acrylate is 70:30.

[0045] Comparative Example 3 The difference from Example 1 is that only sodium acrylate is grafted.

[0046] Comparative Example 4 Compared with Example 1, the difference is that the homopolymers of CMC, N-vinylpyrrolidone, lithium acrylate, 3-acrylamidophenylboronic acid, and glycerol monomethacrylate are physically mixed, while the mass ratio and molar ratio remain unchanged.

[0047] Comparative Example 5 The difference from Example 1 is that CMC is used directly without any modification.

[0048] Application Examples 1-5 and Comparative Application Examples 1-5 The modified CMC or CMC samples obtained in Examples 1-5 and Comparative Examples 1-5 were used to prepare silicon-doped aqueous negative electrode slurry, lithium battery negative electrode sheets, and assemble lithium-ion batteries according to the same steps below: (1) Slurry preparation: The modified CMC or CMC samples obtained in Examples 1-5 and Comparative Examples 1-5 were dissolved in deionized water to prepare a 2wt% adhesive solution. The active material, conductive agent, binder, and SBR were mixed in a mass ratio of 95:2:1.2:1.8, wherein the active material was a mixture of artificial graphite and SiOx, and SiOx accounted for 8% of the mass of the active material. The conductive agent SuperP was added to the adhesive solution and stirred and dispersed for 1 hour; the active material was added in two batches and stirred for 3 hours; finally, the SBR emulsion was added and stirred at low speed for 30 minutes. The solid content of the slurry was adjusted to 48% with deionized water, and the slurry was degassed under vacuum and passed through a 150-mesh sieve to obtain a silicon-doped anode aqueous slurry.

[0049] (2) Coating and drying: The slurry is evenly coated on an 8μm copper foil, and the surface density on one side is controlled to be 9mg / cm. 2 After drying at 80℃ for 15 minutes, it was then vacuum dried at 110℃ for 4 hours.

[0050] (3) Roller pressing: Roller pressing until the compaction density is 1.6 g / cm³ 3 Cut into lithium battery negative electrode sheets.

[0051] (4) Battery assembly: Using lithium metal sheet as counter electrode, polypropylene microporous membrane as separator, and 1.0 mol / L LiPF6 solution of ethylene carbonate / methyl ethyl carbonate / diethyl carbonate (volume ratio 3:5:2) with 10 vol% fluoroethylene carbonate (FEC) added, CR2032 button half cell was assembled in an argon glove box.

[0052] Application Example 6 Compared to Application Example 1, the difference lies in the pulping step, where a hydrolyzed styrene-maleic anhydride copolymer solution (styrene-maleic anhydride copolymer hydrolyzed to a water-soluble salt by dilute LiOH solution, pH 8-9, solid content 15wt%) is added to the slurry before adding SBR. The amount of hydrolyzed SMA is 15% of the mass of the modified CMC. After stirring evenly, the SBR emulsion is added. The drying step involves drying at 80℃ for 15 minutes followed by curing at 110℃ for 4 hours.

[0053] The modified CMC, silicon-doped aqueous anode slurry, lithium battery anode sheet, and lithium-ion battery prepared in the examples and comparative examples were subjected to the following performance tests, and the results are shown in Table 1 and... Figure 1 As shown: (1) Grafting rate test: The product was extracted by Soxhlet, purified by dialysis and dried to constant weight (the difference between two weighings was <0.5%) and then weighed. The grafting rate %G = (W1-W0) / W0×100%, where W0 is the CMC mass of the raw material and W1 is the mass of the purified product.

[0054] (2) Grafted side chain composition test: The modified CMC of Example 1 was analyzed by FT-IR using a JASCO FT-IR-5300 infrared spectrometer with a scanning range of 4000~500 cm⁻¹. -1 Samples were prepared using the KBr tableting method.

[0055] (3) Slurry viscosity test: After the slurry is prepared, let it stand to defoam and measure the viscosity at 25°C using a Brookfield rotational viscometer, referring to GB / T 10247-2008.

[0056] (4) Slurry settling stability test: The slurry was sealed and left to stand at 25°C for 48 hours. The solid content of the upper and lower layers of slurry was measured and the difference between the solid content of the upper and lower layers was calculated.

[0057] (5) Electrode 180° peel force test: According to GB / T 2790-1995, the electrode is cut into 25mm wide strips and peeled at 50mm / min at 180°.

[0058] (6) Peel strength test after immersion in electrolyte: The electrode is immersed in the electrolyte described in Application Example 1, left to stand at 25°C for 24 hours, then removed and the surface electrolyte is dried with filter paper. After the residual solvent is evaporated at room temperature, the peel strength is measured according to method (5).

[0059] (7) Room temperature self-healing efficiency test: Cut the electrode with a blade, fit the cross-section together, and let it stand at room temperature (25℃) for 4 hours. Then test the peeling force according to method (5). Recovery rate = peeling force after self-healing / original peeling force × 100%.

[0060] (8) Electrochemical performance test: voltage window 0.005~1.5V, first activate with 0.1C charge and discharge for 2 cycles, then cycle with 0.5C for 200 cycles. The initial coulombic efficiency is the ratio of the discharge capacity to the charge capacity of the first cycle at 0.1C; the capacity retention rate is the ratio of the discharge capacity of the 200th cycle to the discharge capacity of the 3rd cycle.

[0061] (9) Electrode thickness expansion rate test after cycling: After the battery is cycled 100 times, it is disassembled in the glove box, and the thickness of the negative electrode is measured. The expansion rate is (h-h0) / h0×100%, where h0 is the electrode thickness before cycling.

[0062] Table 1 Performance test results of the examples and comparative examples

[0063] As shown in Table 1, the CMC main chain with medium to low substitution degree used in Example 1 retains a large number of free hydroxyl groups, providing sufficient grafting sites; time-division feeding ensures uniform incorporation of the four monomers. Among them, the NVP structural unit acts as a dispersing conductive agent, and lithium acrylate anchors SiOx and transports Li. + 3-Acrylamidophenylboronic acid and glycerol monomethacrylate structural units form dynamic crosslinks of borate esters. The lithium salt type avoids Na... + The pollution levels are balanced across the board. Example 2 has a low total monomer content and a grafting rate of only 108%, resulting in insufficient functional side chain density. Low NVP leads to weak dispersion, and low levels of lithium acrylate and borate ester units result in weak anchoring and crosslinking, significantly reducing cycle performance. Example 3 has the highest grafting rate of 215%, dense side chains, enhanced dispersion and crosslinking, and excellent cycle performance. Viscosity decreases slightly with increasing grafting rate but remains within the suitable range for coating processes. Example 4 has the highest NVP ratio and the best dispersion. However, the proportions of lithium acrylate, 3-acrylamidophenylboronic acid, and glycerol monomethacrylate are too low, resulting in insufficient anchoring and dynamic crosslinking. During long-term cycling, it cannot constrain silicon expansion, and the capacity retention rate is only 74.5%. Example 5 is the opposite of Example 4, with slightly weaker dispersion, but the strongest lithium acrylate anchoring and borate ester crosslinking, achieving a self-healing efficiency of 90% and excellent cycle performance. This demonstrates that the proportion of 3-acrylamidophenylboronic acid and glycerol monomethacrylate is key to dynamic crosslinking performance.

[0064] Comparative Example 1 uses highly substituted CMC, resulting in fewer free hydroxyl groups and insufficient grafting sites; it has strong water absorption, making it difficult to control the moisture content of the slurry. It lacks dispersion and dynamic crosslinking, exhibiting the worst cycling performance. Comparative Example 2 only has NVP dispersion and lithium acrylate anchoring, lacking dynamic crosslinking of borate esters. The hydrogen bond network in the electrolyte is easily disrupted, and silicon expansion leads to irreversible structural damage, resulting in a capacity retention of only 65.2%. Comparative Example 3 only grafts sodium acrylate, introducing Na into the sodium salt form. + Impurities preferentially reduce and worsen SEI at low potentials; and lacking NVP dispersion units, it exhibits poor sedimentation stability and limited functionality. Comparative Example 4 is a physical mixture without covalent bonds; the polymers are thermodynamically incompatible, leading to migration and phase separation in the slurry. The copolymer exhibits diluted viscosity, uneven functional distribution, localized stress concentration, and the worst performance. The unmodified CMC in Comparative Example 5 has a single function, only thickening and assisting in bonding. The lack of dispersion units causes conductive agent sedimentation; lacking Li + Conductivity optimization; no dynamic crosslinking buffers silicon expansion. Application Example 6 adds hydrolyzed SMA to Example 1 and cures at 110°C to form a dual network of irreversible esterification crosslinking and reversible borate ester crosslinking. The irreversible network enhances cohesion and electrolyte resistance, while the reversible network maintains dynamic response, resulting in optimal cycling performance. Self-healing efficiency is slightly reduced due to the limitation of irreversible crosslinking on fully reversible recombination.

[0065] from Figure 1 It can be seen that in the FTIR spectrum of the modified CMC, at 1660 cm⁻¹... -1 The characteristic peak of the C=O stretching vibration of N-vinylpyrrolidone lactam was detected at 1560 cm⁻¹. -1 and 1420cm -1 Characteristic peaks of asymmetric and symmetric stretching vibrations of lithium acrylate carboxylate were detected at 1730 cm⁻¹. -1 The characteristic peak of the carbonyl C=O stretching vibration of glycerol monomethacrylate was detected at 1380 cm⁻¹. -1 Characteristic peaks of stretching vibrations of 3-acrylamidophenylboronic acid or its borate ester formed with glycerol monomethacrylate were detected. The simultaneous appearance of these characteristic peaks indicates that all four monomers have been grafted onto the CMC backbone.

[0066] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A modified CMC for use in aqueous slurry of silicon-doped anode for lithium batteries, characterized in that, The modified CMC has a medium-low degree of substitution CMC as the main chain, and copolymer side chains are grafted onto the main chain. The copolymer side chains contain N-vinylpyrrolidone, lithium acrylate, 3-acrylamidophenylboronic acid and glycerol monomethacrylate structural units.

2. The modified CMC for the aqueous slurry of silicon-doped anode in lithium batteries as described in claim 1, characterized in that, The degree of substitution of the medium-low degree CMC is 0.6 to 0.8, and the grafting rate of the modified CMC is 50% to 250%.

3. The modified CMC for the aqueous slurry of silicon-doped anode in lithium batteries as described in claim 1, characterized in that, The molar ratio of N-vinylpyrrolidone, lithium acrylate, 3-acrylamidophenylboronic acid and glycerol monomethacrylate is (60~80):(15~30):(2~5):(2.4~7.5).

4. The method for preparing modified CMC for silicon-doped anode aqueous slurry of lithium batteries according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Dissolve carboxymethyl cellulose in deionized water to prepare a solution with a concentration of 0.5~2.0wt%, and heat it to 40~50℃ under nitrogen protection; (2) Add the total amount of N-vinylpyrrolidone monomer and glycerol monomethacrylate accounting for 1 / 3 to 2 / 3 of the total amount of feed; (3) Add some initiator and add lithium acrylate aqueous solution in batches or slowly and continuously to the reaction system within 0~90 min; add initiator and the full amount of 3-acrylamidophenylboronic acid solution and the remaining glycerol monomethacrylate within 60~90 min of reaction; (4) The reaction is carried out at 40~50℃ under nitrogen protection. The total reaction time from the addition of the initiator is 2~5h. (5) The reaction was terminated, and the modified CMC was obtained by precipitation, washing, purification and drying.

5. The method for preparing modified CMC for silicon-doped anode aqueous slurry of lithium batteries as described in claim 4, characterized in that, The lithium acrylate aqueous solution is prepared by neutralizing acrylic acid with LiOH to a pH of 7.0-8.0, and should be prepared before use. The 3-acrylamidophenylboronic acid solution is prepared by adding 3-acrylamidophenylboronic acid to deionized water and adjusting the pH to 8-8.5 with dilute LiOH solution to dissolve it, and should be prepared before use. The initiator is ammonium persulfate or an ammonium persulfate / ascorbic acid redox system, with a total amount of 0.5-3 wt% of the total monomer mass, added in two parts: the first part is added at the beginning of the reaction, and the second part is added after 60 min of reaction.

6. The method for preparing modified CMC for silicon-doped anode aqueous slurry of lithium batteries as described in claim 4, characterized in that, The purification includes methanol Soxhlet extraction and dialysis, wherein the dialysis is performed under pH ≤ 7 conditions and the dialysis is performed using a dialysis bag with a molecular weight cutoff of 8000~14000 Da; the drying is freeze drying or vacuum drying at ≤ 40℃.

7. The application of the modified CMC as described in any one of claims 1 to 3 or the modified CMC prepared by the preparation method as described in any one of claims 4 to 6 in the preparation of aqueous slurry for silicon-doped anodes of lithium batteries, characterized in that, The modified CMC is used in combination with styrene-butadiene rubber latex, and the active material of the silicon-doped anode includes graphite and silicon-oxygen materials, with the silicon-oxygen materials accounting for 3% to 15% of the total mass of the active material.

8. The application as described in claim 7, characterized in that, The slurry also contains hydrolyzed styrene-maleic anhydride copolymer, which is then cured at 100-120°C after coating, allowing the hydrolyzed styrene-maleic anhydride copolymer to undergo in-situ esterification crosslinking with the modified CMC.

9. A lithium battery negative electrode sheet, characterized in that, This includes the modified CMC as described in any one of claims 1 to 3 or the modified CMC prepared by the preparation method described in any one of claims 4 to 6.

10. A lithium-ion battery, characterized in that, It includes the lithium battery negative electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Adhesive for lithium ion battery

    CN105504169A